1997
DOI: 10.2165/00003088-199732030-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Clinical Pharmacokinetics of X-Ray Contrast Media

Abstract: Pharmacokinetic studies of contrast media are usually performed as preclinical trials in anaesthetised animals; however, results in humans have also been reported for this type of compounds. This paper reviews the existing data about x-ray contrast media in humans. In some cases, animal data are used in areas where no human data are available. The administration of contrast media is generally made via the intravenous, intra-arterial or intrathecal route. Diagnostic procedures are based on differential distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 53 publications
2
77
0
1
Order By: Relevance
“…However, PPCPs are present at enzyme-subsaturating levels, which necessitate an oligotrophic metabolism (Daughton and Ternes 1999). Moreover, the chemical structure of some PPCPs is very complex and strong, as for example in the case of the X-ray contrast media iopromide, which has been designed for remaining unaltered during its application and is thus mainly excreted unchanged (Bourin et al 1997).…”
Section: Biological Transformationmentioning
confidence: 99%
“…However, PPCPs are present at enzyme-subsaturating levels, which necessitate an oligotrophic metabolism (Daughton and Ternes 1999). Moreover, the chemical structure of some PPCPs is very complex and strong, as for example in the case of the X-ray contrast media iopromide, which has been designed for remaining unaltered during its application and is thus mainly excreted unchanged (Bourin et al 1997).…”
Section: Biological Transformationmentioning
confidence: 99%
“…The nonionic contrast molecules show no measurable binding to plasma proteins. They are rapidly distributed in the body and almost completely recovered unmetabolized in urine within 24 h [4].…”
Section: Types Of X-ray Contrast Mediamentioning
confidence: 99%
“…Most iopamidol is excreted in the urine (24). The disappearance of the renal enhancement peak observed after liposomal encapsulation showed that the usual mechanism used to clear the iodinated agent was altered by encapsulation.…”
Section: Discussionmentioning
confidence: 99%